2017
DOI: 10.1016/j.cell.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: A Regulated Cell Death Nexus Linking Metabolism, Redox Biology, and Disease

Abstract: Summary Ferroptosis is a form of regulated cell death characterized by the iron-dependent accumulation of lipid hydroperoxides to lethal levels. Emerging evidence suggests that ferroptosis represents an ancient vulnerability caused by the incorporation of polyunsaturated fatty acids into cellular membranes, and that cells have developed complex systems that exploit and defend against this vulnerability in different contexts. The sensitivity to ferroptosis is tightly linked to numerous biological processes, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
4,352
3
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 4,821 publications
(4,740 citation statements)
references
References 112 publications
68
4,352
3
11
Order By: Relevance
“…Human HT-1080 fibrosarcoma cells are a classic ferroptosis model that express wild-type p53 (Dixon et al, 2012; Stockwell et al, 2017; Tarunina and Jenkins, 1993). To characterize the effects of p53 expression on ferroptosis in these cells, we used CRISPR/Cas9 technology to isolate a clonal TP53 knockout ( TP53 KO ) cell line.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human HT-1080 fibrosarcoma cells are a classic ferroptosis model that express wild-type p53 (Dixon et al, 2012; Stockwell et al, 2017; Tarunina and Jenkins, 1993). To characterize the effects of p53 expression on ferroptosis in these cells, we used CRISPR/Cas9 technology to isolate a clonal TP53 knockout ( TP53 KO ) cell line.…”
Section: Resultsmentioning
confidence: 99%
“…System x c − is a cystine/glutamate antiporter whose constitutive activity suppresses ferroptosis in many cell types (Dixon et al, 2012; Stockwell et al, 2017). System x c − -mediated cystine import is necessary for the synthesis of the antioxidant tripeptide (reduced) glutathione (GSH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, ribosome degradation has been observed during apoptotic cell death (13,14,60). Recently, a form of programed cell death in mammalian cells termed ferroptosis (61) has been related to the induction of an excessive lipid damage via iron-dependent peroxidation (reviewed in (62). Understanding the role of iron in ferroptosis is far from complete (48).…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis Ferroptosis is an iron-dependent cell death pathway that involves specific lipid peroxidation patterns that are involved in plasma membrane rupture [9]. However, the precise mechanisms of how lipid peroxidation actually causes the membrane to disintegrate are elusive.…”
Section: The Lipid Peroxidation/autoxation-controlled Necrosis Systemmentioning
confidence: 99%